Heritage in conflict (Leuven)
xxvi, 239 sayfa
Keywords: “Proceedings of two meetings: “Heritage in conflict: a review of the situation in Syria and Iraq“, workshop held at the 63rd Rencontre Assyriologique Internationale, Marburg, Germany, 24-25 July 2017 and “Syria: ancient history - modern conflict“, symposium held at the School of Historical and Philosophical Studies, University of Melbourne, Australia, 11-13 August 2017“ -- ““The Syrian and Iraqi civil wars, with their immense toll of human suffering, have also fuelled an unprecedented wave of heritage destruction. The deliberate ruin of cultural property in Syria and Iraq by the self-proclaimed Islamic State (also referred to as IS, ISIS, ISIL or Da’esh) and other belligerents – widely broadcast across traditional and social media – has horrified heritage professionals and the general public alike. How the heritage community reacted is now coming under increasing scrutiny. The low impact of some projects and, indeed, the total ineffectiveness of others has been highlighted by various commentators. Now is the time to evaluate our responses, reflecting on the successes and failures, in the hope of making future efforts more effective. It is intended that this volume will contribute to this process. This book reflects the proceedings of two workshops, held in Marburg and Melbourne in 2017, that dealt with these matters, and the contributions provide a range of insights into the problems (and solutions) involved. Rather than lengthy formal papers, they offer accounts – in many cases first-hand reports or personal reflections – on the situation as it unfolded“ --